Capital Structure, Internationalization and Countries of Destination of Brazilian Companies: An Analysis of the Upstream-Downstream Hypothesis - Rafael Borges Ribeiro; Vinícius Silva Pereira; Karem Cristina de Sousa Ribeiro (BBR: Brazilian Business Review)
This study examines the effect of defining the country of destination of the international debt of Brazilian multinationals, based on the Upstream–Downstream hypothesis. To deepen the discussion of stability suggested by the theory, this paper inserted institutional variables of the target countries of internationalization in econometric models used by previous studies, testing whether the hypothesis Upstream-Downstream remains valid. Starting from a sample involving Brazilian publicly traded multinational and domestic companies between the years 2007 to 2011 and as a statistical method, we performed a regression with panel data. The results show that Brazilian companies when defining the destination countries of internationalization, regardless of these countries presenting higher or lower stability in relation to Brazil, increase their indebtedness. The results showed that among the characteristics present in countries considered as more stable, only the Corruption Perception Index was positively associated with the level of indebtedness of multinationals.